Aluminum profile with high wear strength for electric vehicle
Patent Information
- Application Number
- CN202611343921.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-01
- Publication Date
- 2026-10-09
AI Technical Summary
[0002]现有电动车车架多采用普通铝型材制成,虽然具备重量轻、导热性好的特点,但在实际使用过程中,电动车车架需要承受骑行过程中的振动、冲击以及外界摩擦、腐蚀等作用,普通铝型材的耐磨性能和结构强度往往难以满足长期使用需求,容易出现表面磨损、变形、开裂等问题,尤其是车架的边角及连接节点处,由于存在直角或锐角结构,受力集中,更容易发生损坏,影响电动车的使用寿命和使用安全性
通过合理的结构设计、优选的材料搭配以及精准的工艺控制,有效解决了现有电动车用铝型材耐磨性能差、结构强度不足、防护效果不佳、使用寿命短等问题,整体提升了铝型材的耐磨、抗冲击、耐腐蚀性能,同时保证了铝型材的轻量化优势,适配电动车的使用需求,延长电动车车架的使用寿命,提升骑行安全性和使用体验,具备良好的实用性和推广价值。
Smart Images

Figure CN122877241A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electric vehicle frame support technology, and more specifically, to an aluminum profile for electric vehicles with high wear resistance and strength. Background Technology
[0002] Most existing electric vehicle frames are made of ordinary aluminum profiles. While these profiles are lightweight and have good thermal conductivity, in actual use, they need to withstand vibrations, impacts, external friction, and corrosion during riding. The wear resistance and structural strength of ordinary aluminum profiles are often insufficient for long-term use, leading to surface wear, deformation, and cracking. This is especially true at the edges and joints of the frame, where right angles or acute angles concentrate stress and are more prone to damage, affecting the lifespan and safety of the electric vehicle. Furthermore, the existing composite structure design of aluminum profiles is flawed, with insufficient bonding strength between the base material and the reinforcing layer, making delamination and detachment likely. This further reduces the overall performance of the aluminum profiles, making them unsuitable for the complex operating environment and long-term riding requirements of electric vehicles.
[0003] Furthermore, the protective measures for existing aluminum profiles used in electric vehicles are relatively simple, mostly relying on a single coating for protection. This results in poor sealing performance, allowing external moisture and dust to easily penetrate the aluminum profile, leading to corrosion and oxidation of the core substrate and shortening its lifespan. Simultaneously, the current processing technology for aluminum profiles is inadequate. Unreasonable process parameters in hot-pressing, welding, and spraying lead to unstable overall performance, resulting in insufficient hardness, poor toughness, and a high coefficient of friction. This not only affects the user experience of electric vehicles but may also pose safety hazards due to damage to the aluminum profiles. Moreover, the structural design of existing aluminum profiles lacks specificity and cannot adequately adapt to the installation requirements of different components such as battery mounting, steering wheel support, and rear seat support. This insufficient structural rationality further limits their application in the electric vehicle field. Summary of the Invention
[0004] The purpose of this invention is to provide an aluminum profile for electric vehicles with high wear resistance and strength, so as to solve the problems mentioned in the background art.
[0005] A high-wear-resistant aluminum profile for electric vehicles includes an electric vehicle frame. The frame is composed of multiple protective sleeves welded and fixed together. A protective sleeve support is fixedly installed on one side of the inside of the electric vehicle frame. A battery loading box is fixedly installed on the rear side of the inside of the electric vehicle frame. Side support plates are fixedly installed on both sides of the battery loading box inside the electric vehicle frame. A handlebar support is fixedly installed on one side of the top of the electric vehicle frame. A rear seat support is fixedly installed on the other side of the handlebar support on the top of the electric vehicle frame. The protective sleeves used to form the electric vehicle frame are internally fixed... A core aluminum profile is provided, comprising a composite substrate layer, a surface-reinforced wear-resistant layer, a sealing and protective layer, a core reinforcement component, and an arc-shaped transition structure. The composite substrate layer is integrally formed by the core substrate and the surface-reinforced wear-resistant layer through a hot-pressing composite process. The core substrate is made of 6061 aluminum alloy with a thickness of 1.5-2.0 mm, and the surface-reinforced wear-resistant layer is made of 7075 aluminum alloy with a thickness of 0.3-0.5 mm. The pressure of the hot-pressing composite process is controlled at 15-25 MPa, the temperature is controlled at 450-500℃, and the holding time is 30-60 min. The arc-shaped transition structure is integrally formed at the corners and connection nodes of the aluminum profile, with a transition arc radius of 0.5-1.0mm and no right angles or acute angles at the transition.
[0006] Preferably, the surface-reinforced wear-resistant layer is fixedly sleeved on the outside of the core reinforcement component, and the core substrate is fixedly sleeved on the outside of the surface-reinforced wear-resistant layer. The surface of the surface-reinforced wear-resistant layer is formed with an oxide film by hard anodizing alloying modification treatment. The thickness of the oxide film is 20-30 μm. The oxide film is doped with 3%-5% Si and 1%-2% Cu by mass fraction. The microhardness of the oxide film is not less than HV500. The chemical composition of the core substrate, by mass fraction, includes Mg: 0.8%-1.2%, Si: 0.4%-0.8%, Fe: ≤0.7%, Cu: ≤0.15%, Mn: ≤0.15%, Zn: ≤0.25%, Ti: ≤0.15%, and the remainder is Al. The tensile strength of the core substrate is not less than 200 MPa, the elongation is not less than 10%, and the Brinell hardness is HB50-HB70.
[0007] Preferably, the sealing and protective layer consists of two parts: one part is a continuous weld formed by laser welding sealing treatment of the bonding surface between the core substrate and the surface reinforced wear-resistant layer in the composite substrate layer; the other part is a polyvinyl fluoride protective coating sprayed on the outer surface of the core reinforcement component. The thickness of the polyvinyl fluoride protective coating is 5-8 μm. The chemical composition of the surface reinforced wear-resistant layer, by mass fraction, includes Zn: 5.1%-6.1%, Mg: 2.1%-2.9%, Cu: 1.2%-2.0%, Mn: 0.3%-0.9%, Si: ≤0.4%, Fe: ≤0.5%, Ti: ≤0.2%, with the remainder being Al. The tensile strength of the surface reinforced wear-resistant layer is not less than 500 MPa, the hardness is not less than HV150, and the yield strength is not less than 430 MPa.
[0008] Preferably, the specific process parameters for the hard anodizing alloying modification treatment are as follows: the electrolyte is a sulfuric acid-oxalic acid mixed electrolyte, wherein the mass fraction of sulfuric acid is 15%-20% and the mass fraction of oxalic acid is 5%-8%; the electrolyte temperature is controlled at -5℃ to 0℃; the oxidation voltage is 120-150V; and the oxidation current density is 1.5-2.5A / dm³. 2 The oxidation time is 30-60 minutes. After oxidation, the product is rinsed with deionized water at a temperature of 40-50℃ for 10-15 minutes.
[0009] Preferably, the laser welding seal adopts fiber laser welding technology, with the welding power set to 800-1200W, the welding speed to 1.5-2.5m / min, the weld width to 0.2-0.4mm, the welding depth to 0.3-0.5mm, the welding process using argon gas protection, the argon gas flow rate to 10-15L / min, and the weld after welding being ground, with the surface roughness Ra ≤ 1.6μm.
[0010] Preferably, the polyvinyl fluoride protective coating is prepared by electrostatic spraying, with a spraying voltage of 30-50kV, a spraying distance of 200-300mm, and a spraying temperature of 180-220℃. After spraying, a curing treatment is performed at a curing temperature of 200-230℃ and a curing time of 20-30min. The coefficient of friction of the polyvinyl fluoride protective coating is ≤0.15, and the adhesion meets the Class 1 standard in GB / T9286-1998.
[0011] Preferably, the arc-shaped transition structure is prepared by CNC milling, with a milling speed of 1000-1500 r / min, a feed rate of 0.1-0.2 mm / r, and a milling depth of 0.2-0.5 mm.
[0012] Preferably, the overall density of the core aluminum profile is ≤2.7g / cm³. 3Rockwell hardness ≥ HRB80, impact toughness at room temperature ≥ 15 J / cm 2 After 100,000 cycles of reciprocating friction test, the wear amount is ≤0.02mm, and there are no cracks, peeling and obvious scratches on the surface.
[0013] Preferably, a sealing sleeve is fixedly provided on the outside of the core substrate, and corner reinforcement members are fixedly provided between the four corners of the core substrate and the sealing sleeve. The corner reinforcement members have a triangular cross-section. A square groove is provided between the four corner reinforcement members on the outside of the core substrate. Three side reinforcement members are fixedly provided inside each of the four square grooves. The two sides of the three side reinforcement members are fixedly connected to the core substrate and the sealing sleeve respectively, and divide a single square groove into three gaps with triangular cross-sections.
[0014] Preferably, the bonding strength between the core substrate and the surface reinforced wear-resistant layer of the composite substrate layer is ≥150MPa, the bonding strength between the surface reinforced wear-resistant layer and the surface reinforced wear-resistant layer is ≥120MPa, the waterproof rating of the sealing and protective layer reaches IP65, the salt spray test time is ≥48h, and the aluminum profile does not deform, crack, or peel off in an environment with a temperature of -40℃ to 80℃.
[0015] Compared with the prior art, the advantages of this invention are: Through reasonable structural design, optimized material selection, and precise process control, the problems of poor wear resistance, insufficient structural strength, poor protective effect, and short service life of existing aluminum profiles for electric vehicles have been effectively solved. The overall wear resistance, impact resistance, and corrosion resistance of aluminum profiles have been improved, while ensuring the lightweight advantage of aluminum profiles. This makes them suitable for the use of electric vehicles, extends the service life of electric vehicle frames, and improves riding safety and user experience. It has good practicality and promotional value.
[0016] This aluminum profile features a composite structure consisting of a reinforced wear-resistant surface layer and a core substrate. The surface layer is made of 7075 aluminum alloy and undergoes hard anodizing and alloying modification to form a high-hardness oxide film. Furthermore, the addition of Si and Cu elements further enhances its wear resistance. The microhardness of the oxide film is no less than HV500. After 100,000 cycles of reciprocating friction testing, the wear amount is ≤0.02mm, with no significant surface damage. This effectively resists external friction and scratches during riding, preventing scratches and peeling from appearing on the aluminum profile surface. Compared to existing ordinary aluminum profiles, its wear resistance is significantly improved, enabling it to adapt to the complex environment of long-term outdoor use of electric vehicles, reducing structural damage caused by surface wear, and extending the service life of the aluminum profile.
[0017] The aluminum profile adopts a multi-layer composite structure consisting of a core substrate, a surface reinforced wear-resistant layer, and core reinforcement components. The core substrate is made of 6061 aluminum alloy, and the surface reinforced wear-resistant layer is made of 7075 aluminum alloy. The two are integrally formed through a hot-pressing composite process with precise parameters, resulting in high bonding strength. Corner and side reinforcement components are also incorporated to divide the square groove into triangular gaps, utilizing the stability of triangles to enhance the overall structural strength. The tensile strength of the core substrate is no less than 200MPa, and the tensile strength of the surface reinforced wear-resistant layer is no less than 500MPa. The overall Rockwell hardness is ≥HRB80, and the room temperature impact toughness is ≥15J / cm². 2 It can effectively withstand vibrations, impacts, and pressure from component installation during riding, preventing deformation and cracking of the aluminum profile, ensuring the structural stability and load-bearing capacity of the electric vehicle frame, and improving riding safety.
[0018] The sealing and protective layer combines laser welding sealing with a polytetrafluoroethylene (PTFE) protective coating. Laser welding forms a continuous weld, effectively sealing the interface between the core substrate and the surface reinforced wear-resistant layer, preventing moisture and dust from entering. The PTFE protective coating is prepared using an electrostatic spraying process, achieving a friction coefficient ≤0.15 and adhesion reaching Level 1 standards. This not only further enhances wear resistance but also provides excellent waterproof and corrosion-resistant properties, achieving an IP65 waterproof rating and a salt spray test time ≥48 hours. It exhibits no deformation, cracking, or coating peeling in environments ranging from -40℃ to 80℃, effectively resisting the erosion of external moisture, salt, and other corrosive media. This prevents internal oxidation and corrosion of the aluminum profile, extending its service life and adapting to the usage requirements of different climatic environments.
[0019] The aluminum profiles feature rounded transition structures at the edges and connection points, eliminating right angles or sharp corners to avoid stress concentration and reduce the risk of damage. Precision manufacturing via CNC milling ensures the smoothness and consistency of these transitions. The processing parameters for each component are precisely controlled; processes such as hot-pressing, hard anodizing, laser welding, and electrostatic spraying all have clearly defined parameter ranges to ensure the overall stability of the aluminum profiles and prevent performance defects caused by improper processes. Furthermore, the frame structure includes a battery loading box, side support plates, handlebar support, and rear seat support, precisely adapting to the installation requirements of various electric vehicle components. The rational structural layout enhances the overall practicality and adaptability of the electric vehicle frame, while the core aluminum profile has an overall density of ≤2.7g / cm³. 3 It balances lightweight design with high performance, without increasing the overall weight of the electric vehicle, thus ensuring ease of riding. Attached Figure Description
[0020] Figure 1 This is a schematic diagram of the overall structure of the present invention; Figure 2 This is a schematic cross-sectional view of the overall structure of the present invention; Figure 3 This is a schematic diagram of the core aluminum profile structure of the present invention; Figure 4 This is a schematic diagram of the arc-shaped transition structure of the present invention; Figure 5 This is a schematic diagram of the cross-sectional structure of the core aluminum profile of the present invention; Figure 6 This is a schematic cross-sectional view of the core reinforcement component of the present invention.
[0021] The following are the labels in the diagram: 1. Electric vehicle frame; 10. Protective sleeve support; 11. Side support plate; 12. Battery loading box; 13. Rear seat support; 14. Handlebar support; 2. Core aluminum profile; 20. Core reinforcement; 21. Surface reinforced wear-resistant layer; 22. Core base material; 23. Corner reinforcement; 24. Square channel; 25. Side reinforcement; 26. Sealing sleeve; 27. Arc-shaped transition structure. Detailed Implementation
[0022] Example: Please refer to Figures 1-6 A high-wear-resistant aluminum profile for electric vehicles includes an electric vehicle frame 1, which is composed of multiple protective sleeves welded and fixed together. A protective sleeve support 10 is fixedly installed on one side of the inside of the electric vehicle frame 1, and a battery loading box 12 is fixedly installed on the rear side of the inside. Side support plates 11 are fixedly installed on both sides of the battery loading box 12, a handlebar support 14 is fixedly installed on one side of the top, and a rear seat support 13 is fixedly installed on the other side of the top. A core aluminum profile 2 is fixedly installed inside the protective sleeves. The core aluminum profile 2 includes a composite substrate layer, a surface-reinforced wear-resistant layer 21, and a sealing protective layer. The core reinforcement component 20 and the arc-shaped transition structure 27 are integrally formed by the core substrate 22 and the surface reinforced wear-resistant layer 21 through a hot-pressing composite process. The core substrate 22 is made of 6061 aluminum alloy with a thickness of 1.5-2.0mm, and the surface reinforced wear-resistant layer 21 is made of 7075 aluminum alloy with a thickness of 0.3-0.5mm. The hot-pressing composite pressure is 15-25MPa, the temperature is 450-500℃, and the heat preservation time is 30-60min. The arc-shaped transition structure 27 is integrally formed at the corners and connection nodes of the aluminum profile, with a transition arc radius of 0.5-1.0mm and no right angles or sharp angles.
[0023] In use, the electric vehicle frame 1 is assembled into an overall frame by welding multiple protective sleeves. The protective sleeve support 10 and side support plates 11 provide support and reinforcement for the protective sleeves and the battery loading box 12, respectively. The handlebar support 14 and rear seat support 13 are used to install the handlebars and rear seat, respectively. The core aluminum profile 2, as the core structure of the protective sleeves, ensures basic strength and wear resistance through hot-pressing composite molding of the composite substrate layer. The arc-shaped transition structure 27 disperses stress at the corners, avoiding stress concentration. This structural design achieves stable installation and support for all components of the electric vehicle frame. The composite structure of the core aluminum profile balances lightweight design with high strength and high wear resistance, while the arc-shaped transition structure reduces the risk of damage, thus improving the overall structural stability and service life of the electric vehicle frame and meeting the riding needs of electric vehicles.
[0024] Specifically, the surface-reinforced wear-resistant layer 21 is fixedly sleeved on the outside of the core reinforcement 20, and the core substrate 22 is fixedly sleeved on the outside of the surface-reinforced wear-resistant layer 21. The surface of the surface-reinforced wear-resistant layer 21 is modified by hard anodizing alloying to form an oxide film with a thickness of 20-30μm, doped with 3%-5% Si and 1%-2% Cu, and has a microhardness of not less than HV500. The chemical composition of the core substrate 22, by mass fraction, includes Mg: 0.8%-1.2%, Si: 0.4%-0.8%, Fe: ≤0.7%, Cu: ≤0.15%, Mn: ≤0.15%, Zn: ≤0.25%, Ti: ≤0.15%, with the remainder being Al. The tensile strength is not less than 200MPa, the elongation is not less than 10%, and the Brinell hardness is HB50-HB70.
[0025] In use, the surface-reinforced wear-resistant layer 21 is fitted onto the outside of the core reinforcement component 20, with the core substrate 22 wrapped around it, forming a multi-layered protective structure. An oxide film formed by hard anodizing and alloying modification covers the surface, enhancing surface hardness and wear resistance. Through the material combination and structural design of the surface-reinforced wear-resistant layer 21 and the core substrate 22, the basic strength and toughness of the aluminum profile are ensured, while surface wear resistance is significantly improved. The doping elements in the oxide film further optimize the wear resistance effect, and the chemical composition ratio of the core substrate ensures good mechanical properties, preventing surface wear and structural deformation of the aluminum profile during use and extending its service life.
[0026] Specifically, the sealing and protective layer consists of two parts. One part is a continuous weld formed by laser welding sealing treatment of the bonding surface between the core substrate 22 and the surface reinforced wear-resistant layer 21 in the composite substrate layer. The other part is a polyvinyl fluoride protective coating sprayed on the outer surface of the core reinforcement 20. The thickness of the polyvinyl fluoride protective coating is 5-8μm. The chemical composition of the surface reinforced wear-resistant layer 21, by mass fraction, includes Zn: 5.1%-6.1%, Mg: 2.1%-2.9%, Cu: 1.2%-2.0%, Mn: 0.3%-0.9%, Si: ≤0.4%, Fe: ≤0.5%, Ti: ≤0.2%, with the remainder being Al. The tensile strength is not less than 500MPa, the hardness is not less than HV150, and the yield strength is not less than 430MPa.
[0027] During use, the continuous weld seam formed by laser welding seals the interface between the core substrate 22 and the surface reinforced wear-resistant layer 21, preventing moisture and dust from entering the gap between them and causing delamination and corrosion. A polyvinyl fluoride protective coating covers the outer surface of the core reinforcement 20, providing protection. The chemical composition of the surface reinforced wear-resistant layer 21 ensures high strength and high hardness. This dual-protection design of the sealing and protective layers effectively improves the sealing performance and corrosion resistance of the aluminum profile, preventing internal structural erosion. The mechanical properties of the surface reinforced wear-resistant layer further enhance the overall strength and wear resistance of the aluminum profile, ensuring its long-term stability.
[0028] Specifically, the process parameters for hard anodizing alloy modification are as follows: the electrolyte is a sulfuric acid-oxalic acid mixed electrolyte, wherein the mass fraction of sulfuric acid is 15%-20% and the mass fraction of oxalic acid is 5%-8%; the electrolyte temperature is controlled at -5℃ to 0℃; the oxidation voltage is 120-150V; and the oxidation current density is 1.5-2.5A / dm³. 2 The oxidation time is 30-60 minutes. After oxidation, the product is rinsed with deionized water at a temperature of 40-50℃ for 10-15 minutes.
[0029] During use, the surface-strengthened wear-resistant layer 21 undergoes hard anodizing alloying modification treatment according to the above process parameters. A sulfuric acid-oxalic acid mixed electrolyte, under specific temperature, voltage, and current density, forms a uniform and dense oxide film on the surface of the surface-strengthened wear-resistant layer 21. After oxidation, residual electrolyte is removed by rinsing with deionized water. By precisely controlling the modification process parameters, the thickness of the oxide film is ensured to be uniform, the hardness meets the standard, and the doped elements are evenly distributed. This significantly improves the wear resistance and corrosion resistance of the surface-strengthened wear-resistant layer 21, preventing defects such as oxide film peeling and cracking, and ensuring the surface quality and performance of the aluminum profile.
[0030] Specifically, the laser welding seal adopts fiber laser welding technology, with welding power set at 800-1200W, welding speed at 1.5-2.5m / min, weld width at 0.2-0.4mm, and welding depth at 0.3-0.5mm. Argon gas protection is used during the welding process, with an argon gas flow rate of 10-15L / min. After welding, the weld is ground, and the surface roughness Ra of the weld after grinding is ≤1.6μm.
[0031] During use, fiber laser welding is employed to weld the interface between the core substrate 22 and the surface reinforced wear-resistant layer 21. Argon gas protection is used to prevent metal oxidation during welding, and the weld seam is ground after welding to ensure a smooth surface. By precisely controlling the laser welding process parameters, the weld seam is ensured to be continuous, dense, and of high strength, effectively sealing the interface and preventing the entry of external impurities. The ground weld seam reduces surface protrusions, avoids stress concentration and friction damage, and further improves the sealing performance and structural integrity of the aluminum profile.
[0032] Specifically, the polyvinyl fluoride protective coating is prepared using an electrostatic spraying process with a spraying voltage of 30-50kV, a spraying distance of 200-300mm, and a spraying temperature of 180-220℃. After spraying, a curing treatment is performed with a curing temperature of 200-230℃ and a curing time of 20-30min. The coefficient of friction of this polyvinyl fluoride protective coating is ≤0.15, and its adhesion meets the Class 1 standard in GB / T9286-1998.
[0033] During use, polyvinyl fluoride (PVC) material is uniformly sprayed onto the outer surface of the core reinforcement 20 using an electrostatic spraying process, followed by curing to ensure a tight bond between the coating and the core reinforcement 20. By precisely controlling the electrostatic spraying and curing process parameters, the PVC protective coating is ensured to be uniform, dense, with a low coefficient of friction and strong adhesion. This effectively improves the wear resistance, water resistance, and corrosion resistance of the aluminum profile, preventing the core reinforcement 20 from being corroded. Simultaneously, it reduces the frictional resistance of the aluminum profile surface, minimizing wear during use and extending the service life of the aluminum profile.
[0034] Specifically, the arc-shaped transition structure 27 is prepared by CNC milling, with a milling speed of 1000-1500 r / min, a feed rate of 0.1-0.2 mm / r, and a milling depth of 0.2-0.5 mm.
[0035] During use, the edges and joints of the aluminum profile are milled according to set parameters using CNC milling technology to form an arc-shaped transition structure 27 with a radius of 0.5-1.0mm, without right angles or sharp angles. This precise CNC milling process ensures the dimensional accuracy and smooth surface of the arc-shaped transition structure 27, effectively dispersing the stress at the edges and joints of the aluminum profile, avoiding stress concentration, and reducing cracking and damage caused by impact and vibration during use. It also enhances the overall aesthetics of the aluminum profile and prevents sharp edges from scratching the human body or other parts.
[0036] Specifically, the overall density of core aluminum profile 2 is ≤2.7g / cm³. 3 Rockwell hardness ≥ HRB80, impact toughness at room temperature ≥ 15 J / cm 2 After 100,000 cycles of reciprocating friction test, the wear amount is ≤0.02mm, and there are no cracks, peeling and obvious scratches on the surface.
[0037] When in use, the core aluminum profile 2 serves as the core structure of the electric vehicle frame protective sleeve, and its overall density is controlled to be ≤2.7g / cm³. 3 This ensures the lightweight design of the aluminum profiles, reducing the overall weight of the electric vehicle and improving riding convenience; Rockwell hardness ≥ HRB80, room temperature impact toughness ≥ 15 J / cm 2 This ensures that the aluminum profile has sufficient strength and toughness to withstand vibrations and impacts during riding; the wear and surface condition after 100,000 cycles of reciprocating friction test ensure that the aluminum profile has excellent wear resistance, is not prone to surface damage during long-term use, further extending the service life of the electric vehicle frame and improving its reliability.
[0038] Specifically, a sealing sleeve 26 is fixedly installed on the outside of the core substrate 22. Corner reinforcement members 23 are fixedly installed between the four corners of the core substrate 22 and the sealing sleeve 26. The cross-section of the corner reinforcement members 23 is triangular. Square grooves 24 are opened between the four corner reinforcement members 23 on the outside of the core substrate 22. Three side reinforcement members 25 are fixedly installed inside the four square grooves 24. The two sides of the three side reinforcement members 25 are fixedly connected to the core substrate 22 and the sealing sleeve 26 respectively, and divide a single square groove 24 into three gaps with triangular cross-sections.
[0039] In use, the sealing sleeve 26 wraps around the outside of the core substrate 22, providing a sealing and protective function. Corner reinforcements 23 are fixed at the four corners of the core substrate 22 and the sealing sleeve 26. Side reinforcements 25 divide the square groove 24 into triangular gaps, utilizing the stability of triangles to enhance structural strength. This structural design further enhances the overall structural strength and stability of the core aluminum profile 2. The corner reinforcements 23 specifically improve the load-bearing capacity of the four corners, while the side reinforcements 25 distribute the lateral stress, preventing deformation and cracking of the core aluminum profile 2 during use. Simultaneously, the sealing sleeve 26 further enhances protective performance, ensuring the long-term stable use of the aluminum profile.
[0040] Specifically, the bonding strength between the core substrate 22 and the surface reinforced wear-resistant layer 21 of the composite substrate layer is ≥150MPa, the bonding strength between the surface reinforced wear-resistant layer 21 and the surface reinforced wear-resistant layer 21 is ≥120MPa, the waterproof rating of the sealing and protective layer reaches IP65, the salt spray test time is ≥48h, and the aluminum profile shows no deformation, cracking or coating peeling in an environment with a temperature of -40℃ to 80℃.
[0041] During use, the high bonding strength between the core substrate 22 and the surface reinforced wear-resistant layer 21 prevents delamination and peeling, ensuring the stability of the composite structure. The high waterproof rating and salt spray resistance of the sealing and protective layer effectively resist the corrosion of external moisture and salt. A wide temperature adaptability range ensures that the aluminum profile can be used normally in different climatic environments without deformation, cracking, or coating peeling. These performance indicators further enhance the reliability and applicability of the aluminum profile, extend its service life, and adapt to the needs of electric vehicles in different regions and environments.
[0042] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely preferred examples and are not intended to limit the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high wear-resistant and high-strength aluminum profile for electric vehicles, comprising an electric vehicle frame (1), characterized in that: The electric vehicle frame (1) is composed of multiple protective sleeves welded and fixed together. A protective sleeve support (10) is fixedly installed on one side inside the electric vehicle frame (1). A battery loading box (12) is fixedly installed on the rear side inside the electric vehicle frame (1). Side support plates (11) are fixedly installed on both sides of the battery loading box (12) inside the electric vehicle frame (1). A handlebar support (14) is fixedly installed on one side of the top of the electric vehicle frame (1). A rear seat support (13) is fixedly installed on the other side of the handlebar support (14) on the top of the electric vehicle frame (1). A core is fixedly installed inside the protective sleeves used to form the electric vehicle frame (1). The core aluminum profile (2) includes a composite substrate layer, a surface-strengthened wear-resistant layer (21), a sealing and protective layer, a core reinforcement component (20), and an arc-shaped transition structure (27). The composite substrate layer is integrally formed by the core substrate (22) and the surface-strengthened wear-resistant layer (21) through a hot-pressing composite process. The core substrate (22) is made of 6061 aluminum alloy with a thickness of 1.5-2.0 mm, and the surface-strengthened wear-resistant layer (21) is made of 7075 aluminum alloy with a thickness of 0.3-0.5 mm. The pressure of the hot-pressing composite process is controlled at 15-25 MPa, the temperature is controlled at 450-500℃, and the heat preservation time is 30-60 min. The arc-shaped transition structure (27) is integrally formed at the corners and connecting nodes of the aluminum profile, with a transition arc radius of 0.5-1.0 mm and no right angles or acute angles at the transition.
2. The aluminum profile for electric vehicles with high wear resistance and strength according to claim 1, characterized in that: The surface-reinforced wear-resistant layer (21) is fixedly sleeved on the outside of the core reinforcement component (20), and the core substrate (22) is fixedly sleeved on the outside of the surface-reinforced wear-resistant layer (21). The surface of the surface-reinforced wear-resistant layer (21) is formed with an oxide film by hard anodizing alloying modification treatment. The thickness of the oxide film is 20-30 μm, and the oxide film is doped with 3%-5% Si and 1%-2% Cu by mass. The microhardness of the oxide film is not... Below HV500, the chemical composition of the core substrate (22) by mass fraction includes Mg: 0.8%-1.2%, Si: 0.4%-0.8%, Fe: ≤0.7%, Cu: ≤0.15%, Mn: ≤0.15%, Zn: ≤0.25%, Ti: ≤0.15%, with the remainder being Al. The tensile strength of the core substrate (22) is not less than 200 MPa, the elongation is not less than 10%, and the Brinell hardness is HB50-HB70.
3. The aluminum profile for electric vehicles with high wear resistance and strength according to claim 1, characterized in that: The sealing and protective layer consists of two parts. One part is a continuous weld formed by laser welding sealing treatment of the bonding surface between the core substrate (22) and the surface reinforced wear-resistant layer (21) in the composite substrate layer. The other part is a polyvinyl fluoride protective coating sprayed on the outer surface of the core reinforcement (20). The thickness of the polyvinyl fluoride protective coating is 5-8 μm. The chemical composition of the surface reinforced wear-resistant layer (21) by mass fraction includes Zn: 5.1%-6.1%, Mg: 2.1%-2.9%, Cu: 1.2%-2.0%, Mn: 0.3%-0.9%, Si: ≤0.4%, Fe: ≤0.5%, Ti: ≤0.2%, and the remainder is Al. The tensile strength of the surface reinforced wear-resistant layer (21) is not less than 500 MPa, the hardness is not less than HV150, and the yield strength is not less than 430 MPa.
4. The aluminum profile for electric vehicles with high wear resistance and strength according to claim 1, characterized in that: The specific process parameters for the hard anodizing alloying modification treatment are as follows: the electrolyte is a sulfuric acid-oxalic acid mixed electrolyte, wherein the mass fraction of sulfuric acid is 15%-20% and the mass fraction of oxalic acid is 5%-8%; the electrolyte temperature is controlled at -5℃ to 0℃; the oxidation voltage is 120-150V; and the oxidation current density is 1.5-2.5A / dm³. 2 The oxidation time is 30-60 minutes. After oxidation, the product is rinsed with deionized water at a temperature of 40-50℃ for 10-15 minutes.
5. The aluminum profile for electric vehicles with high wear resistance and strength according to claim 1, characterized in that: The laser welding seal adopts fiber laser welding technology, with welding power set at 800-1200W, welding speed at 1.5-2.5m / min, weld width at 0.2-0.4mm, and welding depth at 0.3-0.5mm. Argon gas protection is used during the welding process, with an argon gas flow rate of 10-15L / min. After welding, the weld is ground, and the surface roughness Ra of the weld after grinding is ≤1.6μm.
6. The aluminum profile for electric vehicles with high wear resistance and strength according to claim 1, characterized in that: The polyvinyl fluoride protective coating is prepared by electrostatic spraying with a spraying voltage of 30-50kV, a spraying distance of 200-300mm, and a spraying temperature of 180-220℃. After spraying, it is cured at a temperature of 200-230℃ for 20-30min. The coefficient of friction of the polyvinyl fluoride protective coating is ≤0.15, and its adhesion meets the Class 1 standard in GB / T9286-1998.
7. The aluminum profile for electric vehicles with high wear resistance and strength according to claim 1, characterized in that: The arc-shaped transition structure (27) is prepared by CNC milling, with a milling speed of 1000-1500 r / min, a feed rate of 0.1-0.2 mm / r, and a milling depth of 0.2-0.5 mm.
8. The aluminum profile for electric vehicles with high wear resistance and strength according to claim 1, characterized in that: The overall density of the core aluminum profile (2) is ≤2.7g / cm³. 3 Rockwell hardness ≥ HRB80, impact toughness at room temperature ≥ 15 J / cm 2 After 100,000 cycles of reciprocating friction test, the wear amount is ≤0.02mm, and there are no cracks, peeling and obvious scratches on the surface.
9. The aluminum profile for electric vehicles with high wear resistance and strength according to claim 1, characterized in that: A sealing sleeve (26) is fixedly provided on the outside of the core substrate (22). Corner reinforcement members (23) are fixedly provided between the four corners of the core substrate (22) and the sealing sleeve (26). The cross-section of the corner reinforcement members (23) is triangular. A square groove (24) is provided between the four corner reinforcement members (23) on the outside of the core substrate (22). Three side reinforcement members (25) are fixedly provided inside the four square grooves (24). The two sides of the three side reinforcement members (25) are fixedly connected to the core substrate (22) and the sealing sleeve (26) respectively, and the single square groove (24) is divided into three gaps with triangular cross-sections.
10. A high-wear-resistant aluminum profile for electric vehicles according to any one of claims 1-9, characterized in that: The bonding strength between the core substrate (22) and the surface reinforced wear-resistant layer (21) of the composite substrate layer is ≥150MPa, the bonding strength between the surface reinforced wear-resistant layer (21) and the surface reinforced wear-resistant layer (21) is ≥120MPa, the waterproof rating of the sealing and protective layer reaches IP65, the salt spray test time is ≥48h, and the aluminum profile does not deform, crack or peel off in an environment with a temperature of -40℃ to 80℃.